Ethics in practice: the state of the debate on promoting the social value of global health research in resource poor settings particularly Africa. - Lairumbi, G; Michael, P; Fitzpatrick, R; English, M (2011)
BACKGROUND: Promoting the social value of global health research undertaken in resource poor settings has become a key concern in global research ethics. The consideration for benefit sharing, which concerns the elucidation of what if anything, is owed to participants, their communities and host nations that take part in such research, and the obligations of researchers involved, is one of the main strategies used for promoting social value of research. In the last decade however, there has been intense debate within academic bioethics literature seeking to define the benefits, the beneficiaries, and the scope of obligations for providing these benefits. Although this debate may be indicative of willingness at the international level to engage with the responsibilities of researchers involved in global health research, it remains unclear which forms of benefits or beneficiaries should be considered. International and local research ethics guidelines are reviewed here to delineate the guidance they provide. METHODS: We reviewed documents selected from the international compilation of research ethics guidelines by the Office for Human Research Protections under the US Department of Health and Human Services. RESULTS: Access to interventions being researched, the provision of unavailable health care, capacity building for individuals and institutions, support to health care systems and access to medical and public health interventions proven effective, are the commonly recommended forms of benefits. The beneficiaries are volunteers, disease or illness affected communities and the population in general. Interestingly however, there is a divide between "global opinion" and the views of particular countries within resource poor settings as made explicit by differences in emphasis regarding the potential benefits and the beneficiaries. CONCLUSION: Although in theory benefit sharing is widely accepted as one of the means for promoting the social value of international collaborative health research, there is less agreement amongst major guidelines on the specific responsibilities of researchers over what is ethical in promoting the social value of research. Lack of consensus might have practical implications for efforts aimed at enhancing the social value of global health research undertaken in resource poor settings. Further developments in global research ethics require more reflection, paying attention to the practical realities of implementing the ethical principles in real world context.